Concordance, intra- and inter-observer agreements between light microscopy and whole slide imaging for samples acquired by EUS in pancreatic solid lesions. Issue 11 (November 2019) - Larghi, Alberto; Fornelli, Adele; Lega, Stefania; Ragazzi, Moira; Carlinfante, Gabriele; Baccarini, Paola; Fabbri, Carlo; Pierotti, Paola; Tallini, Giovanni; Bondi, Arrigo; de Biase, Dario
Abstract: Background: No study has compared the performance of light microscopy (LM) and whole slide imaging (WSI) for endoscopic ultrasound (EUS) histological acquired tissue samples from pancreatic solid lesions (PSLs). We evaluated the concordance between LM and WSI and the inter- and intra-observer agreements among pathologists on PSLs EUS acquired samples. Methods: LM and WSI from 60 patients with PSLs were evaluated by five expert pathologists to define: diagnostic classification, presence of a core, number and percentage of lesional cells. Washout period between evaluations was 3 months. Time of the procedures was also assessed. Results: Forty-eight cell-block and 12 biopsy samples were evaluated. A high concordance between LM and WSI was found. Inter- and intra-observer agreements for diagnostic classification were substantial and complete, respectively. For all the other parameters, the inter-observer agreement was usually higher for LM. For the intra-observer, a substantial agreement was reached regarding the presence of tissue core and the number and the percentage of malignant cells. Median time for performing LM was significantly shorter than for WSI (p < 0.0001). Conclusions: LM and WSI of cell-block and biopsy samples acquired by EUS in PSLs were highly concordant, with a substantial inter-observer and a complete intra-observer agreements regarding diagnostic classification.